Grounded Theory as a General Research Methodology - Judith A. Holton (Grounded Theory Review: An International Journal, 2008)
Since its inception over forty years ago, grounded theory has achieved canonical status in the research world (Locke, 2001, p.1). Qualitative researchers, in particular, have embraced grounded theory although often without sufficient scholarship in the methodology (Partington, 2000, p.93; 2002, p.136). The embrace renders many researchers unable to perceive grounded theory as a general methodology and an alternative to the dominant qualitative and quantitative research paradigms. The result is methodological confusion and an often unconscious remodelling of the original methodology (Glaser, 2003). Given the various interpretations and approaches that have been popularised under the rubric of grounded theory, this paper addresses the important distinction between grounded theory as a general methodology and its popularisation as a qualitative research method. The paper begins with a brief overview of grounded theory’s origins and its philosophical foundations then continues by addressing the basic distinction between abstract conceptualisation as employed in classic grounded theory and the conceptual description approach as adopted by many qualitative researchers. The paper continues with a brief overview of the criteria for judging the quality of classic grounded theory and concludes by detailing its methodological principles.